Insurance of Sports Practitioners - Aknarouss, MOHAMMED LAMINE (Milev Journal of Research and Studies, 2019)
This study examined the position of insurance among sports practitioners, given the important role of sport insurance services in our time. That importance is due to accidents and damage in sport, whether these damages occurred due to a sport or a game instrument. Thus, it is necessary for the athlete to have protection. Hence, sports officials and practitioners must search for guarantees of their rights. We came to define the legal texts that would guarantee the athlete's rights and define his duties. Let sports accidents insurance be of great importance in supporting sports activity and reducing the risks of sports, by providing it with a guarantee for all participants in sports activity and the various aspects of this activity. Therefore, the idea of ​​risks had to be accepted, requiring identification and prevention of risks through insurance.